The Impact of Artificial Intelligence in Healthcare: Potentialities and Challenges - Luna, Daniel R. (Revista del Hospital Italiano de Buenos Aires, 2024)
Artificial Intelligence in healthcare has the potential to streamline diagnoses, personalize treatments and revolutionize medical research. However, it faces ethical and regulatory challenges. Its transformative potential demands responsible and careful implementation to maximize its benefits.